First record of wood-rotting fungal diversity in dry deciduous forest of Savandurga, Karnataka, India - Kumar, B S; Tejashwini, K; Stephen, A; Nagadesi, P K (Plant Science Today, 2026)
Wood-rotting fungi (WRF) are renowned for their ecological roles, medicinal properties and ligninolytic capabilities. A survey was conducted from April 2023 to December 2024 in the Savandurga dry deciduous forest, Ramanagara district of Bengaluru, Karnataka, India, an area characterised by dense bamboo groves, shrubs and diverse tree species. The study aimed to collect, identify and document WRF using an integrative approach to morphological analysis. The survey identified 32 wood-rotting fungal species associated with different hosts, which includes Arcyria denudata Fr., Auricularia auricula-judae (Bull.) Quél., Coprinellus disseminatus (Pers.) J.E. Lange, Cantharellus spathularia (Schwein.) Schwein., Daldinia concentrica (Bolton) Ces. & De Not., Entonaema splendens (Berk. & M.A. Curtis) Lloyd, Fomitopsis quercina (L.) Spirin & Miettinen, Fulvifomes robiniae (Murrill) Murrill, Fuscoporia gilva (Schwein.) T. Wagner & M. Fisch., Ganoderma adspersum (Schulzer) Donk, G. applanatum (Pers.) Pat., G. gibbosum (Blume & T. Nees) Pat., G. lucidum (Curtis) P. Karst., G. sessile Murrill, Pseudofavolus tenuis (Fr.) G. Cunn., Bull., Inonotus obliquus (Fr.) Pilát, Lentinus polychrous Lév., Collybia nuda (Bull.) Z.M. He & Zhu L. Yang, Marasmius haematocephalus (Mont.) Fr., Microporus xanthopus (Fr.) Kuntze, Lentinus sajor-caju (Fr.) Fr., Fabisporus sanguineus (L.) Zmitr., Schizophyllum commune Fr., Stemonitis splendens Rostaf., Trametes gibbosa (Pers.) Fr., Earliella scabrosa (Pers.) Gilb. & Ryvarden, Xylaria hypoxylon (L.) Grev., X. longipes Nitschke, X. polymorpha (Pers.) Grev., were new reports to Savandurga and Candolleomyces asiaticus Asif, Izhar, Niazi & Khalid and Cellulariella acuta (Berk.) Zmitr. & Malysheva are reported for the first time from India macro– and microscopic characteristics provide information about the diversity of wood-rotting fungi in the region.